Tragedy the basics - McEvoy, Sean 1959- (London New York Routledge, 2017)
"Tragedy: The Basics is an accessible and up-to-date introduction to dramatic tragedy. A comprehensive guide for anyone undertaking a study of the genre, it provides a chronological overview of the genre and the history of traffic theory. Integrating a discussion of texts, contexts and theory, it explains the contextual and theoretical issues which affect the interpretation of tragedy in the context of popularly studied key plays in order to show historical change. Covering tragedy from the classics to the present day, it has a glossary of key terms, a chronology and suggestions for further reading and is an ideal starting point for anyone studying tragedy in literature or theatre studies"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Tragedy -- Handbooks, manuals, etc; Tragic, The; Tragedy -- History and criticism -- Theory, etc; Drama -- Technique; Drama -- History and criticism -- Theory, etc